1966
DOI: 10.1083/jcb.29.2.293
|View full text |Cite
|
Sign up to set email alerts
|

MICROTUBULES AND MICROFIBRILS IN MORPHOGENESIS OF THE SCALE CELLS OF EPHESTIA KÜHNIELLA

Abstract: The development of scale cells in insects has been studied from the appearance of the first cytoplasmic projection which forms the scale rudiment. This rudiment contains numerous longitudinally oriented microtubules throughout. Immediately under its outer surface lie a series of adjacent but distinct bundles of longitudinally oriented circa 60-A fibrils with a circa 120-A center-to-center spacing. As the rudiment broadens, the microtubules become distributed near the surface. The rudiment finally becomes extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

1966
1966
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 12 publications
6
48
0
Order By: Relevance
“…On the wing, the scale cell is held by specialised socket cells within a general lamina of cells. 9,10 Cell lines would therefore possibly need to be derived from wing imaginal discs. However, published cell lines from imaginal discs still do not produce scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the wing, the scale cell is held by specialised socket cells within a general lamina of cells. 9,10 Cell lines would therefore possibly need to be derived from wing imaginal discs. However, published cell lines from imaginal discs still do not produce scales.…”
Section: Discussionmentioning
confidence: 99%
“…After the initiation of a scale, the cell would then need to secrete cuticle: scales finally result from the covering of precisely arrayed cell structures with chitin. 9,10 In general, it is clear that Morpho crysalises are not the ideal candidates for cell culture studies; they are far from model species. Most problematic, however, is the concept that each scale on the Morpho wing results from the sacrifice of a living cell: the scale cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case, the reflectors are formed by multiple cells contributing to the same optical structure, and optical improvements probably arose due to incremental changes in the genome, which led directly to incremental changes in chitin deposition. In butterflies, however, developmental studies have shown that individual scales (optical devices) originate from single cells (Overton 1966).…”
Section: The Evolution Of Photonic Scale Structuresmentioning
confidence: 99%
“…We have been aware of structural colours for some time, Newton (1704) having surmised that they were responsible for the iridescence of male peacock tail feathers. Since then they have been found in a diverse range of taxa, including birds (Prum et al 1999;Zi et al 2003;Li et al 2005;Vigneron et al 2006), fishes (Denton & Nichol 1965, 1966, molluscs (Denton & Land 1971), annelids (Parker et al 2001), cnidarians (Welch et al , 2006 and arthropods (Parker 1995;Parker et al 1998Parker & Hegedus 2003;Vigneron et al 2005). Butterflies, however, reveal the most diverse range of reflectors in any taxon, probably because they possess scales that bear complex architectures at the sub-micron level-a very suitable platform for the evolution of structural colours.…”
Section: Introductionmentioning
confidence: 99%